Ascites in a patient with hairy cell leukaemia and carcinoma of breast : a diagnostic challenge - Wint, Wint Thu Nyunt; Azian Naila Md Nor; Noralisa Abdul Karim; Tang, Yee Loong; S Fadilah S Abdul Wahid; Nor Rafeah Tumian (Penerbit Universiti Kebangsaan Malaysia, 2021)
Hairy cell leukaemia (HCL) is a rare indolent B-cell lymphoproliferative disorder. We report a diagnostic challenge in detecting the cause of ascites, which is a rare, unique manifestation of HCL. A 72-year-old lady presented with 1-month-history of pain in left upper abdomen and loss of weight. There was hepatomegaly, splenomegaly, bilateral inguinal lymphadenopathy, anaemia, and lymphocytosis. She was diagnosed as HCL, based on morphology, immunophenotyping of peripheral blood and bone marrow biopsy examination. In 2009, she was diagnosed as carcinoma of breast when she presented with a mass in left breast; and she received treatment. For HCL, she received intermittent chemotherapy (Chlorambucil+ Prednisolone). Her HCL was stable until 2018 when she presented with recurrent ascites which needed frequent, regular peritoneal paracentesis. Since she had HCL and carcinoma of breast, determining the aetiology of ascites was challenging. Possible causes of her ascites included metastatic carcinoma of breast, HCL, cirrhosis of liver with portal hypertension and peritoneal tuberculosis. Cytology of peritoneal fluid showed mature-looking lymphocytes but no malignant cells. Interestingly, flow cytometry analysis of peritoneal fluid showed the presence of clonal B cell population with lambda light chain restriction. Therefore, it was concluded that her ascites was a manifestation of HCL. A few months later, she succumbed to septicaemia. Impact of ascites on disease course of HCL included rapid disease progression, poor prognosis and shortened survival. We highlight the important role of immunophenotyping in addition to cytomorphology to guide us in confirming the aetiology of ascites in a patient with haematological and solid organ malignancies.